Medical students’ attitudes towards music education: an exploratory research in Ningxia / Zhikai Wang ... [et al.] - Zhikai, Wang; Boo, Ho Voon; Yacob, Yusman Yacob; Ying, Lang (Universiti Teknologi MARA, Kedah, 2024)
xMusic education is useful for medical students especially in meeting their psychological needs and reducing stress amidst their busy medical training. A medical studentoriented music education system, as one part of arts, most probably could help to develop an entire medical knowledgeable system, which is strongly associated with education, medicine and life. Hence, the medical students’ knowledge of music and attitudes towards music education need to be understood for strategic and more balanced medical education development. This research aims to explore the medical students’ perception of music and music education, and understand the importance of the integration of music into medical education. Besides, it also hopes to provide a basis for high-quality development of education and its realization. An online questionnaire was done in Ningxia. A total of 1,232 medical students participated in the online survey consisted of more than 20 questions. The findings indicated that the medical students had a positive perceptions of music education. Recommendations are provided for music education in medical universities to benefit the students and the universities.